An introduction to information design - Coates, Kathryn; Ellison, Andy (Lawrence King, 2014)
Information design is the visualization of information through graphic design. This invaluable guide provides a creative, informative, and practical introduction to the general principles of information design. With chapters on understanding the audience, structure, legibility and readability, selection of media, experimentation, and multi-platform delivery, An Introduction to Information Design gives a complete overview of this fundamental aspect of visual communication. Fully illustrated case studies from leading designers provide professional insight into the challenges involved in creating information design for print, interactive, and environmental media. Practical exercises and tips enable the reader to put this learning into practice. This makes it the perfect book for graphic design students as well as design enthusiasts.